2010
DOI: 10.1111/j.1600-0706.2010.18837.x
|View full text |Cite
|
Sign up to set email alerts
|

Trophic matches and mismatches: can polar bears reduce the abundance of nesting snow geese in western Hudson Bay?

Abstract: Climate change driven advances in the date of sea ice breakup will increasingly lead to a loss of spring polar bear foraging opportunities on ringed seal pups creating a phenological trophic ' mismatch ' . However, the same shift will lead to a new ' match ' between polar bears and ground nesting birds. Th is new match will be especially prevalent along the Cape Churchill Peninsula of western Hudson Bay where both polar bears and nesting snow geese are abundant. Easily foraged goose eggs will provide at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…The low number of scats containing eggs is likely due to the fact that most scats were collected outside the nesting period of birds in Svalbard. Recent studies have, however, reported increased predation by polar bears on nests of various ground-nesting birds (Stempniewicz 2006;Drent and Prop 2008;Rockwell and Gormezano 2009;Smith et al 2010), which in some cases are interpreted as an effect of climate change since more bears are being stranded on shore for longer periods with declining seasonal extent of sea ice in many parts of the Arctic in recent years (Rockwell et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The low number of scats containing eggs is likely due to the fact that most scats were collected outside the nesting period of birds in Svalbard. Recent studies have, however, reported increased predation by polar bears on nests of various ground-nesting birds (Stempniewicz 2006;Drent and Prop 2008;Rockwell and Gormezano 2009;Smith et al 2010), which in some cases are interpreted as an effect of climate change since more bears are being stranded on shore for longer periods with declining seasonal extent of sea ice in many parts of the Arctic in recent years (Rockwell et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Since nutrient content of forage decreases rapidly over the course of the growth season, geese that hatch early generally benefit from high nutrient availability in new forage (Sedinger and Raveling ; Cooch et al ., ; Sedinger & Flint, ). Over the past four decades, snow geese at LPB have advanced their date of hatch at a rate of 0.16 days per year (Rockwell et al ., ), perhaps in an attempt to track the phenology of preferred plant species. Future research will evaluate the extent to which phenology of preferred forage species can explain gosling growth responses and gauge how climate change will affect goslings via changes in plant phenology.…”
Section: Discussionmentioning
confidence: 99%
“…2007), and the localized, catastrophic effect on bird populations (Smith et al . 2010; Rockwell et al . 2011; Iverson et al .…”
Section: Population‐level Use Of Terrestrial Food Resourcesmentioning
confidence: 99%